2021
DOI: 10.1007/s40263-021-00837-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Combining Subcutaneous or Intravenous Esketamine and the MAO Inhibitor Tranylcypromine for the Treatment of Depression: A Retrospective Cohort Study

Abstract: Background (Es)ketamine and monoamine oxidase inhibitors (MAOIs), e.g., tranylcypromine, are therapeutic options for treatment-resistant major depression. Simultaneous administration is currently not recommended because of concern about hypertensive crises. Objective Our objective was to evaluate whether changes in systolic blood pressure (SBP), diastolic blood pressure (DBP), and heart rate (HR) during esketamine administration differed between patients who concomitantly received tranylcypromine and those who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
6
0
5
Order By: Relevance
“…In terms of hemodynamics, our results showed that MAP and HR at endotracheal intubation time point in the esketamine group were higher than those in the remifentanil group. However, MAP and HR at endotracheal intubation time decreased signi cantly in remifentanil group compared with administration time, while MAP and HR in esketamine group were stable without signi cant uctuation, which may be related to the cardiovascular excitation effect of esketamine [20]. At the insertion point of bronchoscopy, the elevated level of MAP and HR in remifentanil were signi cantly higher than that in esketamine group, indicating that esketamine provided better circulative stability.…”
Section: Discussionmentioning
confidence: 89%
“…In terms of hemodynamics, our results showed that MAP and HR at endotracheal intubation time point in the esketamine group were higher than those in the remifentanil group. However, MAP and HR at endotracheal intubation time decreased signi cantly in remifentanil group compared with administration time, while MAP and HR in esketamine group were stable without signi cant uctuation, which may be related to the cardiovascular excitation effect of esketamine [20]. At the insertion point of bronchoscopy, the elevated level of MAP and HR in remifentanil were signi cantly higher than that in esketamine group, indicating that esketamine provided better circulative stability.…”
Section: Discussionmentioning
confidence: 89%
“…A única coorte existente até esta data revelou segurança em um número maior de pacientes (n=14) quando comparados ao grupo controle entre pacientes, entretanto, utilizou doses entre 0,25mg/kg e 0,5mg/kg, o que é inferior ao que costuma ocorrer na prática clínica. Ademais, a primeira dose foi administrada por via venosa e as demais por via subcutânea, protocolo divergente dos demonstrados na maioria das evidências [28].…”
Section: Discussionunclassified
“…Σύμφωνα με τουλάχιστον μία μελέτη που έλεγξε τα αποτελέσματα συγχορήγησής του με εσκεταμίνη, διαπιστώθηκε ότι αν και υπήρξαν σημαντικές μεταβολές στην ΑΠ των θεραπευομένων, αυτές δεν ήταν στατιστικά σημαντικές. 45 Κατά συνέπεια η μελλοντική έρευνα μένει να επιβεβαιώσει με ασφάλεια αυτά τα προκαταρκτικά δεδομένα μιας και ορισμένοι αναστολείς της ΜΑΟ εξακολουθούν να χρησιμοποιούνται ακόμη σε ανθεκτικές περιπτώσεις κατάθλιψης.…”
Section: επίδραση του συνδυασμού υποδορίως ή ενδοφλεβίως χορηγούμενης εσκεταμίνης με την τρανυλκυπρομίνηunclassified